Improving the Adolescent Self-Adjustment by Using Information Services and Cooperative Learning: Experimental - Murisal, Fadil Maiseptian, Erna Dewita, Annisa Nabihah Salwi (South Eastern European Journal of Public Health, 2025)
Adolescent’s ability to adapt to their environment will make it easier for them to adapt to members of the society in which they live. Adolescents who cannot adjust well will not be able to use their thoughts and attitudes positively. To improve adolescent adjustment, a collaborative approach is needed that can strengthen social interaction, communication, and cooperative skills in adjustment. This research aims to improve adolescents' ability to adapt using information services and cooperative learning. The method used is quantitative with a quasi- experimental approach. The research subjects were teenagers from orphanages throughout Sumatra. The data collection technique used a self-adjustment questionnaire and was analyzed using the wilcoxonsigned rank test and colmogorof-smirnof 2 independent samples. The results of the research showa significant increase in adolescent self-adjustment after being given modificationsto information services and cooperative learning.Sothis modification of services and methods is useful for the adjustment of teenagers in orphanages in Sumatra.